Influence of the Implementation of Information Systems on Performance in Small and Mid-sized Enterprises: an Empirical Study in Colombia - Solano Rodriguez, Omar Javier; García Pérez De Lema, Domingo; Bernal García, Juan J. Jesus (Cuadernos de Administración, 2014)
The study of information systems is a relevant aspect in literature of the company’s competitive factors. On the theoretical base of the literature, this work develops an implementation model of the information systems of small and mid-sized enterprises in Colombia. The model proposed seeks to analyze the impact exerted by the factors of implementing information systems on the dimensions of quality and the individual and organizational performance, determined by the performance of users of information systems. To develop this objective, an empirical study was carried out with information from 107 Colombian SMEs. The statistical contrast of the hypotheses proposed was carried out via multivariate linear regressions through ordinary least squares. The results obtained permit inferring that organizations that offer greater support in the implementation of the information system improve the quality of the system and the quality of the information service; additionally, in terms of costs and operational efficiency, favor the company’s organizational performance. This work contributes to the literature on the measurement of the information system within the context of SMEs, permitting to identify processes of change in the way of measuring their effectiveness and their incidence in the performance variables